General ecosystem health indicators - A scoping review - Gillian Penn; Luís Pedro Carmo; Elena Boriani; Michelle Gallagher; Christi Piper; John Berezowski; Barry J. McMahon; Thomas Jaenisch (CABI, 2024)
Abstract Background: Assessing the health status of a natural ecosystem is important across all natural fields of study. Ecologists have discussed and used a variety of terms to describe the health of ecosystems, yet consistent use or adoption of a set of terms has not been established. A common vernacular is necessary to convey the status of an ecosystem to any audience, particularly to influence policy. The purpose of this review is to explore the terms associated with general ecosystem health metrics. Methods: A scoping literature review was performed within three databases, using a search string informed by place, interest, and outcome, a modified PICO (Place, Interest, Comparison, Outcome) structure. A three-stage review process was conducted, at title only, abstract, and full text, respectively. The second and third stages were conducted by two independent reviewers. Key ecosystem health indicator terms were extracted from the final article list and categorized into composite terms or individual indicators for the assessment of general ecosystem health. Results: The initial search yielded 4733 articles, of which 701 were included for screening at the abstract level. A subsequent full-text review of 118 peer-reviewed articles found 95 distinct indicators and 109 multi-metric index systems that qualify under the study search criteria from a total of 64 scientific journals over 20 years. Conclusions: We found a substantial diversity of ecological health terminologies and concepts, reflecting various scientific traditions and disciplines, which highlight not only the necessity to standardize the language for communication but also the opportunity for cross-fertilization. Single distinct indicators were as frequently used as multi-metric index systems. For academic purposes, this raises the question of how underlying value statements and ethical dimensions differ between integrated health terminologies and concepts. For advocacy, we emphasize the need of a consistent core terminology to improve the effectiveness of our messaging. One Health impact statement The impact of this work is focused on the systematic investigation of the terminology used for integrated health assessment. We carried out a scoping review of integrated ecosystem health terminology across disciplines, including 64 different journals from 2002 to 2022. This work has the potential to improve actionable policies in favor of environmental and ecosystem protection and remediation. This landscape analysis is a step toward the creation of a meaningful vocabulary of ecosystem health indicators, including how terminology descriptors and their use can be understood by different stakeholders across disciplines, with implications on the dimensions of implicit intrinsic and extrinsic value statements. By having a dedicated terminology associated with the health or disease of ecosystems in general, systems can be compared, and a simplified message can be conveyed, thereby enhancing not only the understanding of the importance of the health of ecosystems but also improving the ways in which we promote ecological health.